Peran E-Business Dalam Meningkatkan Penjualan Produk Digital Melalui Marketplace - ernawati, dewi fitriana; muhammad iqbal fasa (LPPM STIE Mujahidin Tolitoli, 2025)
The advancement of Information and Communication Technology (ICT) has significantly transformed the business world, particularly through e-business, which utilizes digital platforms for activities such as marketing, transactions, and customer relationship management. This study aims to explore the role of e-business in increasing digital product sales through marketplace platforms. A qualitative approach with a descriptive design was employed, and data were collected through in-depth interviews and observations of digital product sellers on major marketplaces such as Tokopedia, Shopee, and Lazada. Participants were selected purposively based on their active involvement in digital product sales. Data analysis techniques included data reduction, data presentation, and conclusion drawing. The findings indicate that sellers employ digital marketing strategies such as Search Engine Optimization (SEO), Pay-Per-Click (PPC) advertising, and social media marketing to enhance product visibility. The use of data analytics supports sellers in understanding consumer behavior and tailoring their marketing strategies accordingly. However, intense competition and the difficulty of establishing consumer trust in digital products remain significant challenges. Therefore, sellers must optimize adaptive digital strategies aligned with market trends to improve sales effectiveness. The study concludes that e-business plays a vital role in supporting the growth of digital product sales on marketplace platforms.